Trimodal Race Model Inequalities in Multisensory Integration: I. Basics - Colonius, Hans; Wolff, Felix Hermann; Diederich, Adele (Frontiers in Psychology, 2017)
The race model inequality has become an important testing tool for the analysis of redundant signals tasks. In crossmodal reaction time experiments, the strength of violation of the inequality is taken as measure of multisensory integration occurring beyond probability summation. Here we extend previous results on trimodal race model inequalities and specify the underlying context invariance assumptions required for their validity. Some first simulation results comparing the race model and the superposition model for Erlang distributed random variables illustrate the trimodal inequalities.